Understanding the effect of human capital and decent work for migrants’ integration using PLS-SEM - Mirza Marvel Cequea; Jessika Milagros Vásquez Neyra; Valentina Gomes Haensel Schmitt (PLoS ONE, 2025)
This study investigates the impact of human capital on the integration of Venezuelan migrants in Peru, considering decent work as a crucial mediator. The research involved a sample of 1,193 Venezuelan adults residing in Lima and applied Partial Least Squares Structural Equation Modeling to examine the relationships among human capital, decent work, and integration. Findings reveal that human capital significantly enhances migrant integration, facilitating their participation in the labor market and contribution to the local economy. Decent work emerged as a key factor in promoting integration by providing economic stability and supporting social inclusion. However, Peru’s high level of labor informality restricts migrants’ access to formal and dignified employment, limiting the potential impact of decent work on integration. These results underscore the importance of policies aimed at labor formalization and the recognition of migrant skills, which could maximize migrants’ contributions and foster social cohesion. This study provides insights relevant for policymakers in Latin America, particularly in contexts with high labor informality, to develop effective strategies for the integration of migrant populations.